Answer:31
Explanation:Simplifying
5x + -13 = 4x + 18
Reorder the terms:
-13 + 5x = 4x + 18
Reorder the terms:
-13 + 5x = 18 + 4x
Solving
-13 + 5x = 18 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
-13 + 5x + -4x = 18 + 4x + -4x
Combine like terms: 5x + -4x = 1x
-13 + 1x = 18 + 4x + -4x
Combine like terms: 4x + -4x = 0
-13 + 1x = 18 + 0
-13 + 1x = 18
Add '13' to each side of the equation.
-13 + 13 + 1x = 18 + 13
Combine like terms: -13 + 13 = 0
0 + 1x = 18 + 13
1x = 18 + 13
Combine like terms: 18 + 13 = 31
1x = 31
Divide each side by '1'.
x = 31
Simplifyingx=31